Leadership for leaders - Williams, Michael (London : Thorogood publishing Ltd, 2005)
The book is based on extensive research which challenges accepted norms and encourages fresh thought, it also shows how much talent lies untapped in many organisations and provide new and effective ideas for mobilising all this potential.
Formerly CIP.
Includes bibliographical references.
uaj 05/05/2015
Loan
Keywords: Leadership; Executive ability